Risk Factors Affecting Internet Use in Adolescents: A Literature Review - Maulid, Fika; Harkensia, Linur Steffi (Jurnal Indonesia Sosial Sains, 2024)
In today's time, people spend more time on the Internet for long hours due to the increasing number of exciting Internet applications and the convenience of life provided by such applications. Internet use can be at risk if its use is excessive and can cause dependence and addiction. Suppose internet users have experienced addiction or dependence. In that case, it can cause risk factors that are harmful to mental and physical health, poor school achievement, relationships with family/parents that are less harmonious, and excessive household income conditions. Therefore, it is essential to understand the risk factors arising from excessive internet use. So as to raise awareness about health issues currently affecting young people in vulnerable groups. The literature review of this article was obtained from the online databases Science Direct, SpringerLink, ProQuest, EBSCO, and Pubmed in the publication year 2015-2020. Evidence shows that most research articles explain a lot about the risk factors for someone experiencing excessive internet use due to mental health problems and relationship problems with family/parents that are negative. Risk factors that influence Internet use in adolescents have been described in many previous studies. However, little is known about how many risk factors influence internet use in teens. Therefore, this article will provide a number of critical gaps in the evidence base to be used as a source of information on the development of appropriate interventions and can provide a preventive strategy to reduce excessive Internet use in adolescents.